Analisis Minat Politik Kaum Muda Dalam Menyikapi Pemerintahan Era Jokowi 2019-2023 (Studi kasus pada mahasiswa Jombang) - Binti Nasikhatul Walidaini; Nieke Rudyanty winanda; Hudallah Hudallah (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze the political interest of young people in Jombang during the reign of President Joko Widodo (Jokowi) and the factors that influence the political interest of young people. This type of research is qualitative, this research explores various forms of formal and non-formal political participation carried out by young people. The data collection technique used a purposive method with eight student informants spread across four universities in Jombang. Source of data obtained based on primary data and secondary data. To collect data, researchers used observation techniques, in-depth interviews, and documentation studies. The data analysis model used is data collection, data reduction, data presentation and conclusion. The results of this study indicate that the political participation of young people increased during the Jokowi administration, influenced by information disclosure, access to technology, and contemporary issues that are of concern to the younger generation. Nonetheless, there are still challenges in empowering youth political participation, including structural barriers and lack of representation in public policies. From the results of this study it can be concluded that the importance of empowering youth in the political decision-making process in Indonesia to ensure a more inclusive future of democracy and the factors causing youth's lack of interest in politics include the political perception that it is boring to discuss and follow developments. political and economic education.